2020
DOI: 10.1093/femsle/fnaa050
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate-based herbicide affects the composition of microbes associated with Colorado potato beetle (Leptinotarsa decemlineata)

Abstract: Here, we examined whether glyphosate affects the microbiota of herbivores feeding on non-target plants. Colorado potato beetles (Leptinotarsa decemlineata) were reared on potato plants grown in pots containing untreated soil or soil treated with glyphosate-based herbicide (GBH). As per the manufacturer's safety recommendations, the GBH soil treatments were done 2 weeks prior to planting the potatoes. Later, 2-day-old larvae were introduced to the potato plants and then collected in two phases: fourth instar la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 62 publications
3
22
0
Order By: Relevance
“…In addition, glyphosate may affect ecosystem functions including nutrient cycle and carbon balance, plant growth-promoting microbes (e.g. mycorrhizae and nitrogen-fixing bacteria), microbially mediated plantherbivore and pathogen interactions, and pollination biology depending on the related microbial community composition and its sensitivity to glyphosate (Helander et al, 2018;Gómez-Gallego et al, 2020). An analysis of variability in the amino acid landscape (see methods) shows that the amino acids in the active site of the EPSPS that bind PEP are 23% more conserved than the rest of the amino acid residues (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, glyphosate may affect ecosystem functions including nutrient cycle and carbon balance, plant growth-promoting microbes (e.g. mycorrhizae and nitrogen-fixing bacteria), microbially mediated plantherbivore and pathogen interactions, and pollination biology depending on the related microbial community composition and its sensitivity to glyphosate (Helander et al, 2018;Gómez-Gallego et al, 2020). An analysis of variability in the amino acid landscape (see methods) shows that the amino acids in the active site of the EPSPS that bind PEP are 23% more conserved than the rest of the amino acid residues (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the wide use of glyphosate may have a very large impact on the species diversity and composition of microbial communities not only because of a potential purifying selection effect against sensitive bacteria but also because (i) some bacterial groups may adapt rapidly to become resistant to glyphosate and (ii) glyphosate‐based herbicides may enhance multidrug resistance in bacteria (Liu et al ., 2020). Previous studies have shown that glyphosate can affect the microbiome composition of insects, including bees (Motta et al ., 2018), potato beetles (Gómez‐Gallego et al ., 2020) and birds (Ruuskanen et al ., 2020). Moreover, preliminary results suggest a putative effect in the human (Leino et al ., 2020) and rat (Mesnage et al ., 2019) gut microbiomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although data on glyphosate residues in human gut systems are still lacking 29 , our results suggest that glyphosate residues decrease bacterial diversity and modulate bacterial species composition in the gut. Nevertheless, other studies have shown the impact of glyphosate on microbiomes 14,30,31 . We may assume that long-term exposure to glyphosate residues leads to the dominance of resistant strains in the bacterial community .…”
Section: Discussionmentioning
confidence: 98%
“…Due to its affordable price, effectiveness and broad-spectrum ability to kill weeds, glyphosate has become the most commonly used herbicide worldwide [4][5][6] . Although glyphosate antibiotic properties are known 7,8 , its possible effects on microbiomes [9][10][11] have largely been neglected until recently 10,12 . As microbes have driven eco-evolutionary processes since the origin of life, we note the importance of thoroughly understanding the possible undesirable effects of glyphosate on ecosystem structures, functions and services 13 .…”
Section: Mainmentioning
confidence: 99%